2021
DOI: 10.3390/jcm10235696
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Endorphin and Oxytocin in Patients with Alcohol Use Disorder and Comorbid Depression

Abstract: Background: The neuropeptides β-endorphin and oxytocin are released into the bloodstream as hormones from the pituitary gland but also have an important function as neuroregulators in the forebrain. The blood levels of both polypeptides have been shown to reflect depressive symptoms. β-Endorphin, in particular, is also involved in abstinence from alcohol. Methods: The serum levels of β-endorphin and oxytocin were measured during the early withdrawal phase in patients with alcohol use disorder (AUD) with (N = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…β-Endorfin merupakan salah satu peptida opioid yang muncul dari proopiomelanocortin dan menghasilkan hormon adrenocorticotropic, β-lipotropin dan βmelanocyte-stimulating hormon. Hal ini diidentifikasi dalam nukleus arkuata hipotalamus basal yang memainkan peran penting dalam homeostasis energi (Roschina et al, 2021). Bagian tubuh seperti otak memiliki peran utama dalam mengendalikan fisiologi metabolik, mengintegrasikan informasi dari metabolisme organ lain, mengirimkan proyeksi pengaturan dan mengatur fungsi seluruh tubuh (Liu et al, 2022).…”
Section: Pembahasan Efek Terapi Murottal Terhadap Hormon β-Endorfinunclassified
“…β-Endorfin merupakan salah satu peptida opioid yang muncul dari proopiomelanocortin dan menghasilkan hormon adrenocorticotropic, β-lipotropin dan βmelanocyte-stimulating hormon. Hal ini diidentifikasi dalam nukleus arkuata hipotalamus basal yang memainkan peran penting dalam homeostasis energi (Roschina et al, 2021). Bagian tubuh seperti otak memiliki peran utama dalam mengendalikan fisiologi metabolik, mengintegrasikan informasi dari metabolisme organ lain, mengirimkan proyeksi pengaturan dan mengatur fungsi seluruh tubuh (Liu et al, 2022).…”
Section: Pembahasan Efek Terapi Murottal Terhadap Hormon β-Endorfinunclassified
“…The same can be said about the role of receptors for μand κ-opioid peptides and cannabinoids (CB1), which, similar to substance P (Yang et al, 2014;Lee et al, 2018), also produce interesting effects via the dorsal diencephalic trajectory (Gardon et al, 2014;Boulos et al, 2020;Simmons et al, 2020;Vickstrom et al, 2021;Zapata & Lupica, 2021). We have recently obtained evidence that serum levels of β-endorphin, an endogenous μand δ-opioid receptor agonist (Terenius, 2000), are lower in patients with alcohol use disorder, particularly in those with depressive co-morbidity and correlate with physical aggression (Roschina et al, 2021). As some fibres from the arcuate nucleus, expressing the precursor protein of β-endorphin, pass through the stria medullaris to the medial habenula (Sim & Joseph, 1991) and the serum levels may express the activity of intracerebral release, it is tempting to speculate that this might have something to do with changes in μ-opioid receptors activation in the medial habenula.…”
Section: Considering the Connectivity Via The Habenuloid Complexmentioning
confidence: 99%
“…Recent studies also complicate the interpretation of previous studies showing that alcohol consumption decreases OXT levels ( 9 ). For instance, while one study showed significantly higher OXT levels in blood of patients with AUD ( 99 ), another study found significantly lower OXT levels in AUD patients ( 100 ). The reason for such opposite results needs to be further studied.…”
Section: Harnessing the Endogenous Oxt Systemmentioning
confidence: 99%